Development of a rapid point-of-care dengue virus type 2 infection diagnostic assay using recombinase polymerase amplification and lateral flow device - Meagan A. Prescott; Meagan A. Prescott; Myra T. Koesdjojo; David T. Mandrell; Manoj K. Pastey (Frontiers in Cellular and Infection Microbiology)
IntroductionDengue virus (DENV) is the most rapidly spreading arbovirus globally, with over half of the world’s population at risk of infection. Early and rapid detection is crucial to ensure timely patient care, reduce healthcare burden, and prevent severe disease progression. However, conventional nucleic acid amplification techniques are often unsuitable for low-resource settings due to their equipment and procedural demands.MethodsWe evaluated a real-time reverse transcription recombinase polymerase amplification (RT-RPA) assay for the sensitive and specific detection of DENV serotype 2 (DENV2). The assay was tested using both Twista fluorometer and lateral flow detection (LFD) formats. Analytical sensitivity was determined by probit regression, while specificity was assessed against unrelated viruses and other flaviviruses. Clinical validation was performed using serum, cell culture, and FTA® card samples. Assay robustness was evaluated under varying temperatures and after freeze-thaw cycles.ResultsThe RT-RPA assay reliably amplified DENV2 at concentrations as low as 50 copies per reaction, with LOD₉₅ estimated at 38.48 copies (Twista) and 50.37 copies (LFD). No cross-reactivity was observed with respiratory syncytial virus, influenza, rabbit herpes virus, West Nile virus, or other DENV serotypes (DENV1, DENV3, DENV4). The assay successfully detected multiple DENV2 strains and maintained performance across 33°C–40°C and after repeated freeze-thaw cycles. RNA extracted from FTA® cards was successfully amplified. Clinical validation confirmed accurate detection in serum and cell culture samples, while DENV3-positive blood samples tested negative, reinforcing specificity.DiscussionThe RT-RPA/LFD assay offers a rapid, sensitive, and specific tool for DENV2 detection, compatible with low-resource and field-based settings. Its simplicity, robustness, and portability make it a promising approach for point-of-care diagnostics and outbreak surveillance in endemic regions.